The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/jiec.12941
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the environmental performance of producing soil and surfaces through industrial symbiosis

Abstract: Industrial symbiosis (IS), where different entities collaborate in the management of energy, utilities, materials, or services, has been identified as an approach to improve resource efficiency and circularity in industry. This article assesses the environmental performance of an IS network with firms involved in waste management, soil, surfaces, paper, lumber, and energy. The aim is to highlight the environmental performance of an IS network and pay particular attention to the improved performance for product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…As the life cycle assessment followed the approach for employing LCA to review the environmental performance of IS networks, employing the physical allocation method as outlined in [32], the results could be sensitive to this choice. For example, many previous studies have employed the system expansion approach as outlined in [32]; see e.g., [19,35,42]. However, this study, due to the magnitude of the materials being employed, employs only the physical allocation method.…”
Section: Influence Of Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…As the life cycle assessment followed the approach for employing LCA to review the environmental performance of IS networks, employing the physical allocation method as outlined in [32], the results could be sensitive to this choice. For example, many previous studies have employed the system expansion approach as outlined in [32]; see e.g., [19,35,42]. However, this study, due to the magnitude of the materials being employed, employs only the physical allocation method.…”
Section: Influence Of Methodologymentioning
confidence: 99%
“…Gardening soil is employed as the growing medium in the baseline case [31]. Data for the materials and environmental impacts of gardening soil from the Swedish market were obtained from [35]. The fertilizer used for the hydroponic system is blended into the water bath and recirculated.…”
Section: Baseline (Current Production System)mentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity to employing more conventional blends with higher shares of peat and no industrial by-products was reviewed (labeled Gardening Soil-Incr. Peat), employing data from [27], as no other studies on gardening soil impacts were identified; see Figure 7. As the results suggest, the GHG emissions would increase by over 1000 kg for each scenario utilizing gardening soil with more peat.…”
Section: Data Choicesmentioning
confidence: 99%
“…The growing media was shown to have a significant contribution to the environmental performance of the system. While this study also employed soil with less peat than conventional gardening soil based on [27], a larger share of peat would substantially increase the emissions, as shown in the sensitivity analysis above. Replacing conventional soil with other media was shown to reduce the environmental impacts greatly.…”
Section: Growing Medium and Packagingmentioning
confidence: 99%